CREC: the role of serious games in improving flexibility in thinking in neuropsychological rehabilitation. (14th May 2018) - Colautti, Laura; Baldassini, Davide; Colombo, Vera; Mottura, Stefano; Sacco, Marco; Sozzi, Matteo; Corbo, Massimo; Rusconi, Maria Luisa; Antonietti, Alessandro
Abstract: An exploratory study aimed at testing CREC, a training programme designed for people with cognitive impairments caused by a stroke, is reported. The goal of the programme is to improve flexibility in thinking through a creative approach based on everyday problems. The programme includes two Serious Games (SGs) developed ad hoc, dealing with the transfer of the learned strategies to the home environment. The training was applied to six patients to test if it could bring beneficial effects to them. Before and after the training, patients' neuropsychological functioning, emotional state and level of creativity were assessed. Results showed improvements in memory, logical reasoning and praxic skills. Improvements in quality of life and in creativity emerged as well. At the end of the training, the patients perceived themselves as more efficient in problem solving and recognised that the SGs led them to reflect critically on some aspects of their daily life that they usually took for granted.